Inhibition of Na+, K+-ATPase in the hypothalamus, pons and cerebellum of the offspring rat due to experimentally-induced maternal hypothyroidism. (August 2015) - Koromilas, Christos; Liapi, Charis; Zarros, Apostolos; Tsela, Smaragda; Zissis, Konstantinos M.; Kalafatakis, Konstantinos; Skandali, Nikolina; Voumvourakis, Konstantinos; Carageorgiou, Haris; Tsakiris, Stylianos
Abstract Neurodevelopment is known to be particularly susceptible to thyroid hormone insufficiency and can result in extensive structural and functional deficits within the central nervous system (CNS), subsequently leading to the establishment of cognitive impairment and neuropsychiatric symptomatology. The current study evaluated the effects of gestational and/or lactational maternal exposure to propylthiouracil (PTU)-induced hypothyroidism (as a suggestive multilevel experimental approach to the study of hypothyroidism-induced changes that has been developed and characterized by the authors) on crucial brain enzyme activities of 21-day-old Wistar rat offspring in a CNS region-specific manner. The activities of acetylcholinesterase (AChE), Na+, K+-ATPase and Mg2+-ATPase in the offspring hypothalamus, cerebellum and pons were assessed. The study demonstrated that maternal exposure to PTU (0.05% w/v in the drinking water) during the critical periods of neurodevelopment can result in an inhibition of hypothalamic, pontine and cerebellar Na+, K+-ATPase; a major marker of neuronal excitability and metabolic energy production as well as an important regulator of important systems of neurotransmission. On the other hand, no significant changes in the activities of the herein offspring CNS regions' AChE and Mg2+-ATPase were recorded. The observed Na+, K+-ATPase inhibition: (i) is region-specific (and non-detectable in whole brain homogenetes), (ii) could constitute a central event in the pathophysiology of clinically-relevant hypothyroidism-associated developmental neurotoxicity, (iii) occurs under all examined experimental schemes, and (iv) certainly deserves further clarification at a molecular and histopathological level. As these findings are analyzed and compared to the available literature, they also underline the need for the adoption and further study of Na+, K+-ATPase activity as a consistent neurochemical marker within the context of a systematic comparative study of existing (and novel) simulation approaches to congenital and early age hypothyroidism.